Partial Nephrectomy Versus Radical Nephrectomy for Endophytic Renal Tumors: Comparison of Operative, Functional, and Oncological Outcomes by Propensity Score Matching Analysis - Xiong, Situ; Jiang, Ming; Jiang, Yi; Hu, Bing; Chen, Ru; Yao, Zhijun; Deng, Wen; Wan, Xianwen; Liu, Xiaoqiang; Chen, Luyao; Fu, Bin (Frontiers in Oncology, 2022)
Purpose: To compare operative, functional and oncologic outcomes for entophytic renal tumors (ERTs) between partial nephrectomy (PN) and radical nephrectomy (RN) by propensity score matching (PSM) analysis. Methods： A total of 228 patients with ERTs received PN or RN were assessed from August 2014 to December 2021. PSM at a 1:1 ratio was conducted to balance the differences between groups. Perioperative characteristics, renal functional and oncologic outcomes were compared with the groups. Univariate and multivariate Logistic and Cox proportional hazard regression were used to determine the predictors of functional and survival outcomes. Results： After PSM, 68 cases were matched in the PN group and the RN group, respectively. Patients received RN had shorter OT, less EBL, lower high-grade complications (all p＜0.05) than those who received PN. However, better perseveration of renal function was observed in the PN group, which reflected in 48-h postoperative AKI (44.1% vs. 70.6%, p＝0.002), 1-year postoperative 90% eGFR preservation (45.6% vs. 22.1%, p＝0.004) and new-onset CKD Stage ≥ III at last follow-up (2.9% vs. 29.4%, p＜0.001). RN was the independent factors of short-term (OR, 2.812; 95% CI, 1.369-5.778; p＝0.005) and long-term renal function decline (OR, 10.242; 95% CI, 2.175-48.240; p＝0.003). Furthermore, PN provided a better OS and similar PFS and CSS compared with RN (p＝0.042, 0.15 and 0.21, respectively). RN (OR, 7.361; 95% CI, 1.143-47.423; p＝0.036) and pT3 stage (OR, 4.241; 95% CI, 1.079-16.664; p＝0.039) were the independent predictors for overall mortality. Conclusion： For patients with ERTs, although PN has a higher incidence of high-grade complications than RN, when technology is feasible and surgeons are experienced, PN should still be preferred for the better preservation of renal function, longer OS and similar oncologic outcomes.